Three new widely distributed and polymorphic species of Amynthas earthworms (Oligochaeta, Clitellata, Megascolecidae) from South China - Sun, Jing; Jiang, Ji-Bao; Wu, Juzhen; Yuan, Zhu; Qiu, Jiang-Ping (Zootaxa, 2021)
Three new earthworm species are described from South China, namely Amynthas rusticanus sp. nov., Amynthas scaberulus sp. nov., and Amynthas yuanjiangensis sp. nov. They are widely distributed in South China, and be polymorphic in reproductive organs. Of three new species, A. rusticanus sp. nov. is a small species with three pairs of spermathecal pores in 5/6–7/8 or two pairs of spermathecal pores in 5/6–6/7; it has developed prostate glands in XVI–XX. A. scaberulus sp. nov. is a medium-sized species with two pairs of spermathecal pores in 7/8–8/9; the lower edge of each spermathecal pore forms a tiny papilla, and the prostate glands are either degenerated or developed. A. yuanjiangensis sp. nov. is a medium-sized species with four pairs of spermathecal pores in 5/6–8/9 and has degenerated or developed prostate glands. Barcode data for each species (partial sequence of mitochondrial cytochrome c oxidase subunit I) are provided as well.